National Efforts in Climate Change Adaptation in Agriculture: Assessing Policies and Practices in Egypt’s Nile Delta - Raafat, Youssef (AUC Knowledge Fountain, 2025)
Climate change significantly threatens global security and environmental stability, impacting various sectors, especially the agricultural sector (IPCC, 2021). Climate change has already diminished Egypt’s agricultural productivity by 15 percent (Nassr et al., 2021). In response, the Egyptian government has intensified its efforts to increase agricultural practices adaptation, such as Egypt's 2050 Climate Strategy, the National Water Resources Plan (NWRP 2017-2037), and the NWFE program (NCCS, 2022; NWRP, 2017; NWFE, 2022). Nevertheless, the national policies and efforts remain underexplored in the literature, and their evaluations are not accessible to the public (Grindle, 2017). This research aims to assess the extent to which national climate change policies have encouraged a change in agricultural adaptation practices in Egypt’s Nile Delta. The study employs a qualitative exploratory approach, gathering data through semi-structured interviews with stakeholders, including farm owners, government stakeholders, and experts, to analyze their perspectives on how these policies have induced change (Neuman, 2014). The findings of this research indicate that there is a disconnect between policy and on-ground implementation in Egypt, derived from crucial aspects such as the absence of robust policy implementation mechanisms, institutional incoherence, and insufficient climate change awareness among farmers (Grigorieva et al., 2023; Patel & Mwangi, 2023). The research stresses the importance of improving adaptation in agricultural practices through enhanced policy implementation mechanisms to ensure that the agricultural sector achieves optimal productivity (Smit & Olesen, 2013). The recommendations include developing transparent and accountable evaluation frameworks for policies and institutions, fostering public-private partnerships, increasing capacity-building programs, and implementing a hybrid system between centralized and decentralized institutional systems (Grindle, 2017; FAO, 2021).